PENGARUH SELF-EFFICACY TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA DI SEKOLAH DASAR INKLUSI SE-GUGUS III KASIHAN BANTUL - Nur Aziza; Danuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low level of mathematical concept understanding among students in inclusive elementary schools and the importance of psychological factors in supporting learning success. Self-efficacy is considered one of the internal determinants that influence students' confidence in completing academic tasks. This study aims to analyze the effect of self-efficacy on the mathematical concept understanding of students in inclusive elementary schools in Cluster III Kasihan, Bantul. This study employed a quantitative approach with a survey design. The research sample consisted of 114 fifth-grade students selected from a population of 170 students using the Isaac and Michael table with a 5% error rate. The instruments used were a self-efficacy questionnaire and a mathematical concept understanding test that had been declared valid and reliable. The data were analyzed using simple linear regression with the assistance of SPSS. The results showed that the regression equation was Y = 55.779 + 0.210X, with t-count = 2.326 > t-table = 1.98 (Sig. 0.022 < 0.05) and F-count = 5.409 > F-table = 3.93, indicating that self-efficacy has a positive and significant effect on students’ mathematical concept understanding. However, the relationship is relatively low (R = 0.215), with the contribution of self-efficacy to mathematical concept understanding being 4.6%, or 3.8% after adjustment (Adjusted R² = 0.038), indicating that most of the variation is influenced by other factors outside this study.